Applying Interactive, Islamic Methods Enhances Students' Noble Character Understanding - Fadillah, M Renaldy; U Abdullah Mu’min; Azizi Abu Bakar; Anisa Aulia; Yusup Maulana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to evaluate the effectiveness of interactive learning methods based on Islamic values in improving the understanding of noble character among fifth-grade students at MI Al Hasanah, with a focus on the values of honesty, responsibility, and politeness. Using a qualitative approach with a case study design, data were collected through participatory observation, semi-structured interviews with 20 students and three teachers, and analysis of learning documents. Data triangulation and thematic analysis based on Miles and Huberman (1994) were conducted to ensure validity. The results showed that interactive methods, such as group discussions, inspirational stories, and Quran-based simulations, increased student engagement by 90% and moral understanding scores from 65 to 82. Ninety percent of students demonstrated positive behavioral changes, with a 60% reduction in inter-student conflicts. Teacher training was identified as a key factor in the success of this method. The study concluded that this method is effective in shaping student character, with recommendations for developing instructional guidelines and teacher training for sustainability.